Neuroimaging evaluations of olfactory, gustatory, and neurological deficits in patients with long-term sequelae of COVID-19 - Masala, Carla; Porcu, Michele; Orofino, Gianni; Defazio, Giovanni; Pinna, Ilenia; Solla, Paolo; Ercoli, Tommaso; Suri, Jasjit S.; Spinato, Giacomo; Saba, Luca (Brain imaging and behavior, 2024)
The World Health Organization indicated that around 36 million of patients in the European Region showed long COVID associated with olfactory and gustatory deficits. The precise mechanism underlying long COVID clinical manifestations is still debated. The aim of this study was to evaluate potential correlations between odor threshold, odor discrimination, odor identification, and the activation of specific brain areas in patients after COVID-19. Sixty subjects, 27 patients (15 women and 12 men) with long COVID and a mean age of 40.6 ± 13.4 years, were compared to 33 age-matched healthy controls (20 women and 13 men) with a mean age of 40.5 ± 9.8 years. Our data showed that patients with long COVID symptoms exhibited a significant decrease in odor threshold, odor discrimination, odor identification, and their sum TDI score compared to age-matched healthy controls. In addition, our results indicated significant correlations between odor discrimination and the increased activation in the right hemisphere, in the frontal pole, and in the superior frontal gyrus. This study indicated that the resting-state fMRI in combination with the objective evaluation of olfactory and gustatory function may be useful for the evaluation of patients with long COVID associated with anosmia and hyposmia.